Energy performance of residential buildings design - Danielski, Itai (Mittuniversitetet, Avdelningen för ekoteknik och hållbart byggande, 2016)
Through the history of civilization, humans have built shelters to practice their social activities, while having protection against weather, wild animals, and other human beings. Over the course of time, vernacular dwellings have evolved to respond to climate challenges, available materials and cultural expectations in a given location. Such buildings include, e.g. the adobe house, the Inuit igloos in Greenland, and the open courtyard building design.Since the start of the postmodern architecture, in the middle of the 20th century, new technologies, new materials, and changes in societal structures have changed the way buildings have been designed and constructed. Modern lifestyle become more dependent on energy. For example Heating, Ventilation and Air Conditioning systems (HVAC) in buildings became widely used to improve indoor comfort. After the oil-supply crises in the middle of the 1970s, the connection between building design and the environment changed from just providing sufficient thermal comfort to promoting energy efficiency due to the awareness of the fact that natural resources are limited. That was the start of the sustainable architecture movement. It was during this time building regulations in many countries started to include aspects of energy efficiency. This chapter will discuss two aspects of building design and their effect on the overall energy efficiency of the building: the interior building design and the exterior building design.